Pilgrimage Traditions During The Period Of Temurids - Abdukadirov Jasurbek (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The active participation of muslim individuals in travel from the first periods of islamic history shows that there is a positive view of travel in islam. In islamic philosophy, it is believed that God’s glory can be understood by seeing the richness and beauty of the things he has created. At the same time, traveling and participating in tourism activities allow people to feel better, relieve stress and thus perform better.